Dampak Kekeliruan dalam Pemilihan Kode KBLI pada Akta Pendirian PT Bagi Notaris dan Pelaku Usaha - Sarungu, Gabriella Tiku; Disriani Latifah Sorindah (LPPM Universitas Ekasakti Padang, 2024)
Business activities in various fields of business are now increasing from national to international scale, especially those related to the establishment of a legal entity, namely a Limited Liability Company (PT). These activities are inseparable from the need for the necessary authentic deeds. One of the authentic deeds that continues to be needed in the community is a deed of establishment of a legal entity in the form of a PT. In making the deed of establishment of PT, there are things that need to be considered, especially regarding the use of the Indonesian Standard Business Field Classification (KBLI) code which is single purpose. If there is an error in the use of the 2020 KBLI code, it will have an impact on the processing of licenses for business actors. Specifically, the purpose of this research is to find out and further understand the consequences of errors in the selection of the 2020 KBLI code on the deed of establishment of a PT. This research is conducted using the doctrinal research method, namely research based on applicable laws and regulations. This research produces two sides of the consequences, namely the consequences experienced by Notary and the consequences experienced by Business Actors. The consequences experienced by the Notary for errors in the application of the KBLI code are authentic deeds that can be degraded or reduced to underhand deeds and the Notary can be held civilly liable if proven guilty. Meanwhile, the consequences experienced by business actors are losses in terms of material and business activities that want to run are not running because they do not get permission from the relevant agencies for the use of several types of KBLI codes that are single purpose in one entity.